Contribution to the identification of the species Myrcia hatschbachii D. Legrand (Myrtaceae): anatomical and histochemical analyses - Gatto, Larissa Junqueira; Bobek, Vanessa Barbosa; Budel, Jane Manfron; Fabri, Natasha Tiemi; Dias, Josiane de Fatima Gaspari; Miguel, Obdulio Gomes; Miguel, Marilis Dallarmi (Ciência e Natura, 2021)
The genus Myrcia is used in folk medicine to treat diabetes. The plants used in folk medicine require morphological and anatomical references to attest to its authenticity. This is the first report of the microscopic study of Myrcia hatschbachii. In this sense, the aim of the present study was to describe the anatomical characteristics, in order to contribute to the species' identification. For anatomical and surface analyses free-hand sections were prepared and observed using optical microscopy, simultaneously some materials were processed and observed under scanning electron microscopy. In addition, histochemical tests were performed. The anatomical features described here correspond with previously reported features found in other species of the genus Myrcia. Furthermore, the following anatomical markers were observed in Myrcia hatschbachii: druses in the spongy parenchyma, concave-convex midrib, heart-shaped petiole, oval-shaped stem, C-shaped vascular bundle in the midrib and open arc shape with invaginated ends in the petiole; phenolic compounds in the phloem and lignified cells in the pith. The results of anatomical and histochemical analyses provide micromorphological and microchemical features that can help in the taxonomy and proper identification of the species.